Mechanical Ventilation and the Titer of Antibodies as Risk Factors for the Development of Transfusion-Related Lung Injury. (4th June 2012) - Vlaar, A. P. J.; Kuipers, M. T.; Hofstra, J. J.; Wolthuis, E. K.; Wieland, C. W.; Roelofs, J. J. T. H.; Boon, L.; Schultz, M. J.; Lutter, R.; Juffermans, N. P.
Abstract : Purpose . Onset of transfusion-related acute lung injury (TRALI) is suggested to be a threshold-event. Data is lacking on the relation between titer of antibodies infused and onset of TRALI. We determined whether onset of TRALI is dependent on the titer of MHC-I antibodies infused in a combined model of ventilator-induced lung injury and antibody-induced TRALl. Methods . BALB/c mice were ventilated for five hours with low (7.5 ml/kg) or high (15 ml/kg) tidal volume. After three hours of MV, TRALI was induced by infusion of 0.5 mg/kg, 2.0 mg/kg or 4.5 mg/kg MHC-I antibodies. Control animals received vehicle. After five hours of MV, animals were sacrificed. Results . MV with high tidal volumes resulted in increased levels of all markers of lung injury compared to animals ventilated with low tidal MV. In ventilator-induced lung injury, infusion of 4.5 mg/kg of antibodies further increased pulmonary wet-to-dry ratio, pulmonary neutrophil influx and pulmonary KC levels, whereas infusion of lower dose of antibodies did not augment lung injury. In contrast, mice ventilated with low tidal volumes did not develop lung injury, irrespective of the dose of antibody used. Conclusions . In the presence of injurious MV, onset of TRALI depends on the titer of antibodies infused.